The effects of convenience and speed in m-payment - Teo, A.C.; Tan, G.W.H.; Ooi, K.B.; Hew, T.S.; Yew, K.T. (Emerald, 2015)
Purpose - The purpose of this paper is to uncover the effects of perceived transaction convenience (PTC) and perceived transaction speed (PTS) on unified theory of acceptance and use of technology (UTAUT) in the context of m-payment. Design/methodology/approach - A predictive analysis approach was used to examine the PTC and PTS using a two-stage partial least square (PLS) and neural network (NN) analyses. Findings - The findings reveal that only effort expectancy (EE) and facilitating conditions (FC) were discovered to significantly influence BI. More importantly, PTC was found to have positive significant relationship with EE and performance expectancy (PE). Moreover, PTS also supported the positive relationship with BI and EE. Practical implications - The findings of the study provided further insights to mobile payment service providers, online banking industry players, and all decision makers and stakeholders involved. Originality/value - Despite of many attempts devoted to understand m-payment adoption, the effects of PTC and PTS on m-payment are not well understood.